PENYULUHAN DAN SOSIALISASI PENGELOLAAN SAMPAH DI DESA TERATAK - Isnaeni, Lira Mufti Azzahri; Elfian, Elfian (COVIT (Community Service of Tambusai), 2021)
Effective waste management can be started from the management of waste sorting independently by the community. However, to increase public awareness to want to manage waste independently is not easy and requires a long time. Because just providing additional knowledge is not enough, so it is necessary to carry out activities to provide skills to the community so that they are able and have the awareness to do waste sorting independently. This community service activity aims to raise public awareness to have a concern for environmental sustainability by not throwing garbage in the river, as well as providing community skills to carry out waste sorting management independently. The target audience involved in this community service activity is the community of RT 3 and RW 1 of Teratak Village, Rumbio Jaya District. This activity was carried out using several methods, namely lectures and questions and answers, Focus Discussion Groups (FDG), and workshops (Independent waste sorting management practices). The training participants are divided into groups of five to ten people. Each group was asked to practice how to sort organic and non-organic waste. Overall, the PKM activities ran smoothly and received a positive response from the participants. Although the ultimate goal for environmental preservation has not yet been achieved, at least the goal to raise awareness, care and provide skills for the people of RT 3 and RW 1 Teratak Village, Rumbio Jaya District to carry out waste sorting management independently can be carried out. Participants have been able to practice household waste sorting independently by separating organic and non-organic waste into the used tire waste bins that have been distributed